Pengaruh Asimetri Informasi, Profitabilitas, dan Ukuran Perusahaan terhadap Manajemen Laba: Studi pada Perusahaan Manufaktur di Indonesia - Puspita Wulandari Dwika; Ruth Samantha Hamzah; Eka Meirawati (JEMBATAN, 2023)
The study aims to examine the effect of information assimetric, profitability, and firm size on the earnings management of basic and chemical industry sectors manufacturing companies listed on the Indonesia Stock Exchange for the year 2016 to 2020. The sampling method employed purposive sampling and collected 33 companies for five years observations, hence we obtained 165 sample observations. Moreover, multiple linear regression is exploited as the analysis method. Based on the results, it is concluded that information assimetric and probability have positive effect on earnings management. Meanwhile, firm size has negative effect on earnings management.